Oil Prices, Exchange Rates and Interest Rates - Lutz Kilian; Xiaoqing Zhou (Center for Economic Studies and ifo Institute (CESifo), 2019)
There has been much interest in the relationship between the price of crude oil, the value of the U.S. dollar, and the U.S. interest rate since the 1980s. For example, the sustained surge in the real price of oil in the 2000s is often attributed to the declining real value of the U.S. dollar as well as low U.S. real interest rates, along with a surge in global real economic activity. Quantifying these effects one at a time is difficult not only because of the close relationship between the interest rate and the exchange rate, but also because demand and supply shocks in the oil market in turn may affect the real value of the dollar and real interest rates. We propose a novel identification strategy for disentangling the causal effects of oil demand and oil supply shocks from the effects of exogenous shocks to the U.S. real interest rate and exogenous shocks to the real value of the U.S. dollar. We empirically evaluate popular views about the role of exogenous real exchange rate shocks in driving the real price of oil, and we examine the extent to which shocks in the global oil market drive the U.S. real exchange rate and U.S. real interest rates. Our evidence for the first time provides direct empirical support for theoretical models of the link between oil prices, exchange rates, and interest rates.
Keywords: E43; F31; F41; Q43; 330; exchange rate; interest rate; oil price; global real activity; commodity; carry trade